(3efgGL GdhUhd Edi TQM eYjGQ GdYbhd aj Yde GdCUhds - (3CMeO Hf jMji Hf GdeQJVj Hf eaVd Hf efUhQ GdMSfj, GdegOj dOjf Gddg,J (B840 (3g` s ((3Ydi Hf eMeO GdMhGdi s)
(3ChdgG (B:s
(3jfHZi bHd GdTQhY ai gPG GdcJGH Cf JaSjQ CdaGX JSejJg HgPG GdGSe hhLggG , afbhd s
(3BNQgG (B:s
(3hef CLd UObgG cdjI ehLHI HYcS Edi LRFjI SGdHI Je s
(3GdefgGL gh GdSaQ GdSGOS ef ZGjGJ GdCacGQ hfgGjGJ GdCfXGQ GdeMjWI HYLGFH GdHMQ GdRNGQs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMI s
(3Ydi WQJgG JedcGJ hahGFO cJHJ HQSe GdbGVi GdeWgQ Hf CMeO Hf YHO Gddg Hf eMeO Hf GdeYGai s
(3bQf GdfSN (B:s
Keywords: (3CUhd Gdabgs